Room temperature alkali activation of fly ash: The effect of Na2O/SiO2 ratio - Bignozzi, M.; Manzi, S.; Natali, M.; Rickard, William; Van Riessen, Arie (ELSEVIER, 2014)
Alkali activation of fly ash can be considered as one of the more promising alternative systems to traditional hydraulic binders, particularly if the process can be carried out at room temperature. With the aim of finding the best solution chemistry for room temperature activation, two types of fly ash have been activated using Na2O/SiO2 molar ratio ranging from 0.12 to 0.20. It was found that the behaviour of the resultant geopolymer and mortars in the fresh and hardened state is more influenced by the type of fly ash, in particular by their fineness and mineralogical composition, than by the increasing proportion of sodium silicate solution in the mix.